How Retroviruses and Retrotransposons in Our Genome May Contribute to Autoimmunity in Rheumatological Conditions - Mustelin, Tomas; Ukadike, Kennedy C. (Frontiers in Immunology, 2020)
More than 200 human disorders include various manifestations of autoimmunity. The molecular events that lead to these diseases are still incompletely understood and their causes remain largely unknown. Numerous potential triggers of autoimmunity have been proposed over the years, but very few of them have been conclusively confirmed or firmly refuted. Viruses have topped the lists of suspects for decades, and it seems that many viruses, including those of the Herpesviridae family, indeed can influence disease initiation and/or promote exacerbations by a number of mechanisms that include prolonged anti-viral immunity, immune subverting factors and mechanisms, and perhaps ‘molecular mimicry’. However, no specific virus has yet been established as being truly causative. Here, we discuss a different, but perhaps mechanistically related possibility, namely that retrotransposons or retroviruses that infected us in the past and left a lasting copy of themselves in our genome still may provoke an escalating immune response that leads to autoimmune disease. Many of these loci still encode for retroviral proteins that have retained some, or all, of their original functions. Importantly, these endogenous proviruses cannot be eliminated by the immune system the way it can eliminate exogenous viruses. Hence, if not properly controlled, they may drive a frustrated and escalating chronic, or episodic, immune response to the point of a frank autoimmune disorder. Here, we discuss the evidence and the proposed mechanisms, and assess the therapeutic options that emerge from the current understanding of this field.